Vidas Secas e desigualdade no Brasil: a atuação do Conselho Nacional de Justiça para a democratização do acesso à Justiça - Pessoa, Flávia Moreira Guimarães (2022)
The interconnection between Law and art and, specifically, between Law and Literature, allows for a better understanding through the legal imagination of people's daily lives and the reality of a given place. In an unequal country like Brazil, the work of Graciliano Ramos, particularly in “Vidas Secas” is a portrait of Brazil's extreme poverty, which is not embraced by constitutional guarantees, in particular access to justice. The National Council of Justice, a constitutional body for the control of the Judiciary Power established by Constitutional Amendment 45 of 2004, has established itself as an inductor of public judicial policies for the democratization of Access to Justice. Based on these premises, this paper will analyze the work developed by the CNJ for the democratization of access to justice based on the problems exposed in the work Vidas Secas. The analysis will be carried out in the light of the constitutional hermeneutics that materialize fundamental rights, having a descriptive nature and based on bibliographical and documentary research of an interdisciplinary nature guided by the inductive method with phenomenological contributions.